Databases Analisa Dan Perancangan Sistem Purwarupa Persediaan Keluar Masuk Barang Baker Old Karang Tengah Menggunakan MySQL Sebagai Database - Aries Saifudin; Kevin Hadikusuma; Muhamad Fajar; Muhammad Iskandar; Rizki Iqfan Apriliansyah (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2023)
Databases or we often spell data base is a collection of records of various parts of knowledge. The database studies information science, a database has a very structured explanation that is stored neatly. The task of the activity this time, the maker is working with an entrepreneurial place with the name BakerOld which is in Ciledug Tangerang, this time the author is contributing to an entrepreneur place that has problems with supplying stock in its warehouse. The author conducts a data analysis and makes a prototype of the supply of goods in and out, which is intended to make it easier to manage the course of production. Application projects can be used by a company that is assisted by hardware and software in internal and external connections. Very different applications have different system requirements and a program can be used and run to copy data when not connected to the internet and then make changes to the new database when connected to the internet. By using MySQL which can provide a private simulation of the internet or a network of various PCs even though they are not connected to a network card or switch. With the use of MySQL this will build a database system. The benefit of the database system is that clients and users can share databases from various servers, so that every change in the database will be stored in the database..